Epigenetic Mechanisms in Apis melifera: From Development to Environmental Adaptation - Xiexin Hu; Jing Xu; Kang Wang (Current Issues in Molecular Biology)
Epigenetics, as an important scientific field that bridges genomic function and phenotypic plasticity, increasingly demonstrates its value in bee research. In recent years, with the rapid development of omics technologies, there have been significant advancements in the study of epigenetics in honeybees. This article reviews the role of epigenetic regulation in the development, behavioral regulation, and immune response of honeybee larvae from the perspectives of DNA methylation, histone modification, and non-coding RNA. With the continuous deepening of related research, honeybee epigenetics not only opens new paths for understanding the formation mechanisms of complex traits in social insects but also provides solid theoretical support and innovative perspectives for the study of social insects and beekeeping practices. These insights also inform sustainable beekeeping practices.